2015
DOI: 10.15252/emmm.201505433
|View full text |Cite
|
Sign up to set email alerts
|

KLF 4 is a key determinant in the development and progression of cerebral cavernous malformations

Abstract: Cerebral cavernous malformations (CCMs) are vascular malformations located within the central nervous system often resulting in cerebral hemorrhage. Pharmacological treatment is needed, since current therapy is limited to neurosurgery. Familial CCM is caused by loss‐of‐function mutations in any of Ccm1, Ccm2, and Ccm3 genes. CCM cavernomas are lined by endothelial cells (ECs) undergoing endothelial‐to‐mesenchymal transition (EndMT). This switch in phenotype is due to the activation of the transforming growth f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
189
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(194 citation statements)
references
References 95 publications
(135 reference statements)
5
189
0
Order By: Relevance
“…Loss-of-function of CCM proteins has also been shown to trigger β-catenin and transforming growth factor beta/bone morphogenetic protein (TGFβ/BMP) signaling-driven endothelial-to-mesenchymal transition (EndMT) (Bravi et al, 2016, Bravi et al, 2015, Guan and Couldwell, 2013, Maddaluno et al, 2013), as well as activation of MEKK3 signaling and increased expression of the mechanosensitive transcription factors KLF2 and KLF4 (Cullere et al, 2015, Cuttano et al, 2016, Fisher et al, 2015; Zhou et al, 2015; Zhou et al, 2016). Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
See 1 more Smart Citation
“…Loss-of-function of CCM proteins has also been shown to trigger β-catenin and transforming growth factor beta/bone morphogenetic protein (TGFβ/BMP) signaling-driven endothelial-to-mesenchymal transition (EndMT) (Bravi et al, 2016, Bravi et al, 2015, Guan and Couldwell, 2013, Maddaluno et al, 2013), as well as activation of MEKK3 signaling and increased expression of the mechanosensitive transcription factors KLF2 and KLF4 (Cullere et al, 2015, Cuttano et al, 2016, Fisher et al, 2015; Zhou et al, 2015; Zhou et al, 2016). Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…Both of these mechanisms have been suggested to be key determinants of CCM disease pathogenesis (Maddaluno et al, 2013, Bravi et al, 2016, Cuttano et al, 2016, Zhou et al, 2016). Moreover, it has been also suggested that increased Rho activity, as well as proteolytic activity of extracellular matrix metalloprotease ADAMTS, arises secondary to increased MEKK3–KLF2/4 signaling during CCM formation (Zhou et al, 2016).…”
Section: Current Knowledge Of the Molecular Basis And Mechanisms Of Cmentioning
confidence: 99%
“…5 A′′-F′′ and U). Previous work showed that KLF2/4 are up-regulated following CCM loss in endothelial cells (29)(30)(31)(32)(33). KLF2/4 signals were increased in the cerebellum of cKO mice, but the drugs did not reverse this effect (Fig.…”
Section: Combined Treatment Reverses Outcomes Of Endothelial Ccm3 Losmentioning
confidence: 80%
“…Mutations of the CCM3 gene have been linked to cerebral cavernous malformations -vascular abnormalities characterised by dilated leaky cerebral lesions that can lead to brain haemorrhage (Draheim et al, 2014). The exact mechanism by which cerebral cavernous malformations arise is still subject to debate, with deregulation of several signalling pathways such as RHO (Richardson et al, 2013;Stockton et al, 2010;Borikova et al, 2010;Whitehead et al, 2009), TGFβ (Maddaluno et al, 2013), β-catenin (Bravi et al, 2015) and MEKK3-KLF2 or MEKK3-KLF4 (Cuttano et al, 2016;Zhou et al, 2016;Renz et al, 2015) having been demonstrated to be involved in development and progression of the disease. Crucially, loss of the CCM3 interaction with GCKIII kinases seems to be the crucial feature of all disease-associated CCM3 mutations (Fidalgo et al, 2010).…”
Section: E-2mentioning
confidence: 99%